2015
DOI: 10.5137/1019-5149.jtn.13788-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic morphometry of internal carotid circulation in turkish children

Abstract: AIm: Knowledge of cerebrovascular morphology is integral in planning neuroendovascular interventions, especially for procedures involving placement of stents, flow diverters or stentrievers. There is insufficient data on angiographic normative values of cerebral circulation in the pediatric age group since angiograms are uncommonly performed in children except for arteriovenous malformations in which arterial dimensions are larger than normal. We aimed to measure the diameters of internal carotid circulation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
(35 reference statements)
1
14
1
Order By: Relevance
“…Available studies document diameters slightly higher than the present study. This difference may be attributed to the inner diameter measured in the present study as compared to outer diameters measured by others [ 19 20 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Available studies document diameters slightly higher than the present study. This difference may be attributed to the inner diameter measured in the present study as compared to outer diameters measured by others [ 19 20 ].…”
Section: Discussioncontrasting
confidence: 89%
“…However, it has been shown that the cranial growth is rapid during the early years of life and then slows markedly with virtual complete growth by the age of 6 years with 85% of growth complete by the age of 5 [25]. Similarly, by the age of 4 years the intracranial arteries have reached 81-99% of their adult diameters with 87% of the middle cerebral artery (MCA) diameter reached by 6 months of age [26]. Similar findings were reported by He et al [27] who dubbed it 'the rule of 5' since the vast majority of the arterial growth occurs before the age of 5.…”
Section: Dissecting and Fusiform Aneurysmsmentioning
confidence: 99%
“…Arat evaluated the anterior circulation in children and found a correlation between age and ICA diameters. 14 Our case met the criteria for an advanced disease and the decision was made to start IAC. Moreover, prior contralateral disease may be associated with a genetic predisposition in this particular patient.…”
Section: Discussionmentioning
confidence: 83%